Complex Formation of N’-[4-(dimethylamino)phenyl]methylene Isonicotinohydrazide with Lanthanide Ions in Water-Dioxane Medium and the Associated Thermodynamics - Sharmeli, Y.; Lonibala, R.K. (Asian Journal of Chemistry, 2010)
Interaction of N’-[4-(dimethylamino)phenyl]methylene isonicotinohydrazide (damINH) with La3+, Pr3+, Nd3+, Sm3+, Eu3+ and Gd3+ ions in 30 % water-dioxane medium has been studied potentiometrically at ionic strength 0.05 M NaClO4 at 20, 30 and 40 °C. The pH-metric titration curve of the ligand shows only one inflection point indicating the presence of only one dissociable proton and the dissociation constant of damINH, log K1 H has been determined from the pHmetric titration data. Formation of only 1:1 metal-ligand complexes is inferred from the metalligand formation curves and the formation constants (log K) evaluated for the Ln(III) complexes, follows the trend: La3+ < Pr3+ < Nd3+ < Sm3+ < Eu3+ > Gd3+, showing a break at Gd. Calorimetric studies are carried out for the Gd3+ complex at 30 °C in 30 % water-dioxane medium and change in enthalpy (DH), n (metal-ligand stoichiometry) and K (stability constant) are obtained by nonlinear least-squares fitting of the calorimetric data. Calorimetric studies also suggest formation of 1:1 Gd(III)-damINH complex. Thermodynamic parameters associated with both the protonation and complexation reactions have been calculated and the values suggest spontaneity and exothermic nature of all the reactions. DS values indicate that the deprotonation of damINH is both enthalpy and entropy-driven process while the complexation reactions are entropically unfavourable.